A structural interpretation of the aftershock "cloud" of the 1992 Mw 7.3 Landers earthquake - Liu, Jing (2013)
We analyze the spatial relationship of relocated aftershocks to the principal rupture planes of the Mw 7.3 1992 Landers mainshock from a structural point of view. We find that the aftershocks constitute primarily a several-kilometer-wide damage zone centered on the mainshock rupture planes. The intensity of damage decreases away from the principal faults. Less than half of the aftershocks occurred within 1 km of the mainshock planes, and perhaps only 5% of the aftershocks are candidates for rerupture of the mainshock faults. Moreover, it seems that aftershocks along the Landers rupture have b-values that correlate well with the complexity of the mainshock rupture. Low b-values occur along segments that are simple, whereas higher b-values correlate with sections that are more complex. Thus, structural complexity appears to correlate with a greater relative abundance of small earthquakes. These observations imply that aftershock populations reflect fault populations in the medium surrounding the principal faults rather than the behavior of the mainshock planes themselves.